WiMAX implementation of smart grid wide area distributed generation and demand side load protection model in MATLAB/SIMULINK - Arefin, Mohammad Kamrul (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.